Diffusion-Weighted Imaging of Cerebritis - Tung, Glenn A.; Rogg, Jeffrey M. (American Journal of Neuroradiology, 2003)
Summary: Restricted water diffusion has been used to distinguish pyogenic abscess from other rim-enhancing brain masses; however diffusion-weighted imaging of cerebral infection before capsule formation has rarely been described. We report a case of fungal cerebritis in which water diffusion was more restricted than that of normal contralateral brain and the measured diffusion coefficient was in the range of that reported for pyogenic brain abscess. In the proper clinical setting, cerebritis should be considered in the differential diagnosis of an ill-defined focal brain mass associated with markedly restricted water diffusion.